IRC data for a mechanistic route starting with H2O adsorption and finishing with H2 desorption from graphene - Andrea Oyarzún; Ximena García; Ljubisa Radovic (Data in Brief, 2020)
Intrinsic reaction coordinate (IRC) data regarding the interactions of water with a carbene-like active site located at the edge of a polyaromatic hydrocarbon [1–3] has been obtained using density functional theory (DFT) and the 6–31g(d) basis set as implemented in the Gaussian 16 software [4]. The data is presented as two videos (frontal and lateral mechanism views) combining four consecutive IRC calculations corresponding to the four different transition states presented on “https://doi.org/10.1016/j.carbon.2020.01.011” [3] (Figure 6, side approach). These videos provide powerful insights on two key aspects: a) the rotational process that occurs during water adsorption and b) the hydrogen gas desorption process during water gasification of carbons.